2022
DOI: 10.3390/antiox11020250
|View full text |Cite
|
Sign up to set email alerts
|

Phytogenotypic Anthocyanin Profiles and Antioxidant Activity Variation in Fruit Samples of the American Cranberry (Vaccinium macrocarpon Aiton)

Abstract: In this study, we conducted an analysis of the qualitative and quantitative composition of anthocyanins and anthocyanidins in different cultivars and genetic clones of American cranberries grown in Lithuanian climatic conditions. Four anthocyanin compounds predominated in fruit samples of American cranberry cultivars: cyanidin-3-galactoside, cyanidin-3-arabinoside, peonidin-3-galactoside, and peonidin-3-arabinoside. They accounted for 91.66% ± 2.79% of the total amount of the identified anthocyanins. The total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 62 publications
(74 reference statements)
0
11
0
Order By: Relevance
“…The authors reported that phenolic acid content did not correlate with the detected antiradical and antioxidant activity, but the content of anthocyanins in cranberries had a moderate positive correlation with the antioxidant activity of cranberry fruit extracts, as determined by the ABTS (r = 0.675, p < 0.05) and the FRAP (r = 0.614, p < 0.05) methods [ 7 ]. Urbštaitė et al found that the correlation between anthocyanin quantity and antioxidant activity assessed by the FRAP method was r = 0.507 ( p < 0.001), and by the ABTS method was r = 0.635 ( p < 0.001) [ 62 ].…”
Section: Resultsmentioning
confidence: 99%
“…The authors reported that phenolic acid content did not correlate with the detected antiradical and antioxidant activity, but the content of anthocyanins in cranberries had a moderate positive correlation with the antioxidant activity of cranberry fruit extracts, as determined by the ABTS (r = 0.675, p < 0.05) and the FRAP (r = 0.614, p < 0.05) methods [ 7 ]. Urbštaitė et al found that the correlation between anthocyanin quantity and antioxidant activity assessed by the FRAP method was r = 0.507 ( p < 0.001), and by the ABTS method was r = 0.635 ( p < 0.001) [ 62 ].…”
Section: Resultsmentioning
confidence: 99%
“…It should be noted that the values of the AA determined by the ABTS assay were always higher than by the FRAP assay both for berries (on average by 37%) and leaves during fruiting (on average by 28%). An approximately 1.5-fold excess of the ABTS over FRAP values (in µmol TE/g FW) has been reported for berries and leaves of various fruit and berry crops [ 22 , 63 , 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…The extraction of anthocyanins and phenolic compounds from cranberry fruit samples was performed according to the methodology described by Urbstaite et al [ 42 , 43 ]. The extraction of triterpenic compounds and phytosterol compounds from cranberry fruit samples was performed according to the methodology described by Sedbare et al [ 44 ].…”
Section: Methodsmentioning
confidence: 99%